Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Ok, I want to find

$$\int\limits_0^t {{e^u}\log udu} $$ and $$\int\limits_0^t {{e^{ - u}}\log udu} $$

I'm thinking as follows

$$d\left( {{e^u}\log u} \right) = {e^u}\log udu + \frac{{{e^u}}}{u}du$$

$$d\left( {{e^{ - u}}\log u} \right) = - {e^{ - u}}\log udu + \frac{{{e^{ - u}}}}{u}du$$

Thus I put

$$\int {{e^u}\log udu} = {e^u}\log u - Ei\left( u \right)$$

$$\int {{e^{ - u}}\log udu} = Ei\left( { - u} \right) - {e^{ - u}}\log u$$

But then I want to integrate over $(0,t)$. My principal concern is proving that for $t\to 0$

$$ Ei\left( { - t} \right) - {e^{ - u}}\log u\to \gamma$$

$${e^u}\log u - Ei\left( t \right) \to -\gamma$$

How would you solve this?

EDIT: Ok I've found that $$Ei(t) = \gamma + \log(t) + z + \frac{z^2}{4} + \cdots + \frac{z^n}{n n!}+\cdots$$

The new question would be: How do I prove such expansion?

I mean, I know that

$$\int \frac{e^x}{x} dx = \log x + \sum_{n>0} \frac{x^n}{n n!}$$

But then again where does $\gamma$ appear? Since $$Ei(t) = \int_{-\infty}^t \frac{e^u}{u} du$$ I'd need to find the limit for $x \to -\infty$, which should be $\gamma$.

Is guess you could also use $$Ei(t) = \log t + \int_0^t {\frac{e^u-1}{u}du}$$ which is a more "natural" definition in the sense the integral is always converging for finite $t$ and the logarithm instantly discloses the discontinuity at $t=0$

share|cite|improve this question
Oops, I mistook derivative for antiderivative. Way past my bedtime. – Henning Makholm Feb 5 '12 at 3:50
I suppose you haven't seen this already... – J. M. Feb 5 '12 at 6:14
up vote 2 down vote accepted

For $\int_0^te^u\log u\,\mathrm{d}u$,

Consider \begin{align*} f(x) &= \int_0^tu^xe^u\,\mathrm{d}u \\ &= \int_0^tu^x\sum\limits_{n=0}^\infty \frac{u^n}{n!}\,\mathrm{d}u \\ &=\int_0^t\sum\limits_{n=0}^\infty\frac{u^{n+x}}{n!}\,\mathrm{d}u\\ &=\left[\sum\limits_{n=0}^\infty\frac{u^{n+x+1}}{n!\,(n+x+1)}\right]_0^t=\sum\limits_{n=0}^\infty\frac{t^{n+x+1}}{n!\,\left(n+x+1\right)}, \end{align*} Then \begin{align*} f'(x) &=\int_0^tu^xe^u\log u\,\mathrm{d}u \\ &=\sum\limits_{n=0}^\infty\frac{t^{n+x+1}\log t}{n!\,(n+x+1)}-\sum\limits_{n=0}^\infty\frac{t^{n+x+1}}{n!\,(n+x+1)^2} \end{align*} Therefore \begin{align*} \int_0^te^u\log u\,\mathrm{d}u =f'(0) &=\sum\limits_{n=0}^\infty\frac{t^{n+1}\log t}{n!\,(n+1)}-\sum\limits_{n=0}^\infty\frac{t^{n+1}}{n!\,(n+1)^2} \\ &=\sum\limits_{n=0}^\infty\frac{t^{n+1}\log t}{(n+1)!}-\sum\limits_{n=0}^\infty\frac{t^{n+1}}{(n+1)!\,(n+1)} \\ &=(e^t-1)\log t-\sum\limits_{n=1}^\infty\frac{t^n}{n!\,n} \end{align*} For $\int_0^te^{-u}\log u\,\mathrm{d}u$,

Consider \begin{align*} g(x) &= \int_0^tu^xe^{-u}\,\mathrm{d}u \\ &=\int_0^tu^x\sum\limits_{n=0}^\infty\frac{(-1)^nu^n}{n!}\,\mathrm{d}u \\ &=\int_0^t\sum\limits_{n=0}^\infty\frac{(-1)^nu^{n+x}}{n!}\,\mathrm{d}u \\ &=\left[\sum\limits_{n=0}^\infty\frac{(-1)^nu^{n+x+1}}{n!\,(n+x+1)}\right]_0^t=\sum\limits_{n=0}^\infty\frac{(-1)^nt^{n+x+1}}{n!\,(n+x+1)} \end{align*} Then \begin{align*} g'(x) &=\int_0^tu^xe^{-u}\log u\,\mathrm{d}u \\ &=\sum\limits_{n=0}^\infty\frac{(-1)^nt^{n+x+1}\log t}{n!\,(n+x+1)}-\sum\limits_{n=0}^\infty\frac{(-1)^nt^{n+x+1}}{n!\,(n+x+1)^2} \end{align*} Therefore \begin{align*} \int_0^te^{-u}\log u\,\mathrm{d}u=g'(0) &=\sum\limits_{n=0}^\infty\frac{(-1)^nt^{n+1}\log t}{n!\,(n+1)}-\sum\limits_{n=0}^\infty\frac{(-1)^nt^{n+1}}{n!\,(n+1)^2} \\ &=\sum\limits_{n=0}^\infty\frac{(-1)^nt^{n+1}\log t}{(n+1)!}-\sum\limits_{n=0}^\infty\frac{(-1)^nt^{n+1}}{(n+1)!\,(n+1)} \\ &=(1-e^{-t})\log t+\sum\limits_{n=1}^\infty\frac{(-1)^nt^n}{n!\,n} \end{align*}

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.